URGENSI PERSIDANGAN SECARA ELEKTRONIK (E-LITIGASI) DALAM PERSPEKTIF HUKUM ACARA PERADILAN AGAMA DI ERA DIGITALISASI - Riyan Ramdani; Dewi Mayaningsih (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2021)
AbstractThe issuance of Supreme Court Regulation Number 1 of 2019 concerning the Administration of Cases and Trials in Courts Electronically (e-litigation) is an attempt by the Supreme Court to realize modern court services based on information technology in the era of digitalization 4.0. The religious court is one of the judicial bodies that organizes electronic trials. Electronic court hearings in religious courts are expected to provide convenience for justice seekers by still referring to the provisions of the procedural law of religious courts which have been the guidelines for trial practice in religious courts. The purpose of this study is to determine the urgency of electronic trial (e-litigation) at the Religious Courts in the era of digitalization 4.0, and to examine the electronic trial (e-litigation) in the perspective of the procedural law of religious courts. The method used in this research is descriptive, with a normative juridical approach, and analysis with library research. From this research, it is known that electronic trials (e-litigation) in religious courts can provide convenience for court apparatus and for the public in conducting trials and electronic trials are a form of simplification of the procedural law of religious courts.Keywords: E-Litigation, Religious Court Procedural Law, Digitization AbstrakLahirnya Peraturan Mahkamah Agung Nomor 1 Tahun 2019 tentang Administrasi Perkara dan Persidangan di Pengadilan Secara Elektronik (e-litigasi) merupakan upaya Mahkamah Agung untuk mewujudkan pelayanan pengadilan yang modern berbasis teknologi informasi di era digitalisasi 4.0. Pengadilan agama menjadi salah satu badan peradilan yang menyelenggarakan persidangan elektronik. Persidangan elektronik di pengadilan agama diharapkan dapat memberikan kemudahan bagi masyarakat pencari keadilan dengan tetap mengacu pada ketentuan hukum acara peradilan agama yang selama ini menjadi pedoman dalam praktik persidangan di pengadilan agama. Tujuan penelitian ini untuk mengetahui urgensi dari persidangan elektronik (e-litigasi) pada Pengadilan Agama di era digitalisasi 4.0, dan untuk mengkaji persidangan elektronik (e-litigasi) dalam perspektif hukum acara peradilan agama. Metode yang digunakan dalam penelitian ini yaitu desktriptif, dengan pendekatan yuridis normatif, dan analisis dengan library research. Dari penelitian ini diketahui bahwa persidangan elektronik (e-litigasi) di pengadilan agama dapat memberikan kemudahan bagi perangkat pengadilan dan bagi masyarakat dalam menyelenggarakan persidangan serta persidangan elektonik merupakan wujud penyederhanaan dari hukum acara peradilan agama.Kata Kunci : E-litigasi, Hukum Acara Peradilan Agama, Digitalisasi